Vibrations in microtubules - Pokorný, J; Jelínek, F; Trkal, V; Lamprecht, I; Hölzel, R (Journal of biological physics, 1997)
Vibrations in microtubules and actin filaments are analysed using amethod similar to that employed for description of lattice vibrationsin solid state physics. The derived dispersion relations show thatvibrations in microtubules can have optical and acoustical branches.The highest frequency of vibrations in microtubules and in actinfilaments is of the order of 10(8) Hz. Vibrations are polar andinteraction with surroundings is mediated by the generatedelectromagnetic field. Supply of energy from hydrolysis of guanosinetriphosphate (GTP) in microtubules and of adenosine triphosphate(ATP) in actin filaments may excite the vibrations.
Keywords: Dispersion relation; Microtubule translation symmetry; Nonlinearity in cytoskeleton; Hydrolysis of GTP; Energy supply to cyto-skeleton; Vibrations in microtubules; Vibrations in actin filaments; Fröhlich's condensation in cytoskeleton; Hydrolysis of ATP